2013
DOI: 10.1155/2013/909045
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Use of Spray and Freeze Drying Techniques for Preparation of Solid Self-Microemulsifying Formulation of Valsartan andIn VitroandIn VivoEvaluation

Abstract: The objective of the present study was to develop self micro emulsifying formulation (SMEF) of valsartan to improve its oral bioavailability. The formulations were screened on the basis of solubility, stability, emulsification efficiency, particle size and zeta potential. The optimized liquid SMEF contains valsartan (20% w/w), Capmul MCM C8 (16% w/w), Tween 80 (42.66% w/w) and PEG 400 (21.33% w/w) as drug, oil, surfactant and co-surfactant, respectively. Further, Liquid SMEF was adsorbed on Aerosol 200 by spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…This method enables entrapment of both hydrophilic and hydrophobic drugs in polymer matrix and compared to other techniques (emulsificationprecipitation, emulsification-cross-linking, ionotropic gelation, solvent evaporation, and coacervation) it might be used in both laboratory and industrial scale. Moreover, it is characterized by the possibility of precisely controlling production parameters, high production yield (40-80%), and encapsulation efficiency (up to 100%) [37][38][39][40]. It was shown that formulated microspheres were characterized by relatively narrow size distribution and MF loading in all formulations was in the range between 37.3±3.8% and 75.6±1.4% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This method enables entrapment of both hydrophilic and hydrophobic drugs in polymer matrix and compared to other techniques (emulsificationprecipitation, emulsification-cross-linking, ionotropic gelation, solvent evaporation, and coacervation) it might be used in both laboratory and industrial scale. Moreover, it is characterized by the possibility of precisely controlling production parameters, high production yield (40-80%), and encapsulation efficiency (up to 100%) [37][38][39][40]. It was shown that formulated microspheres were characterized by relatively narrow size distribution and MF loading in all formulations was in the range between 37.3±3.8% and 75.6±1.4% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The samples included pure PAC, solid carrier (POE 4000), and the PAC loaded solid-nanoemulsion preconcentrate. The samples were placed in standard aluminum pans and then scanned at constant heating rate of 10°C/min between 20 and 450°C under a nitrogen gas flow of 20 mL/min [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The IR spectra were recorded on the FTIR (Jasco FT/IR-410, Japan) by using a potassium bromide pressed disc method. The spectrum was scanned over the frequency range of 4000–400 cm −1 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Particles with high internal friction or cohesion increase the value of angle of repose. Moreover, Carr's index and Hausner's ratio should be less than 20% and 1.25, respectively, to ensure optimal flowability for proniosome powders (Singh, Vuddanda, Singh, & Srivastava, 2013). MDPP showed the lowest angle of repose (25±3°), Carr's index (21±4%) and Hausner's ratio (1.27±0.07) providing the best micromeritics properties among all.…”
Section: Micromeritics Propertiesmentioning
confidence: 98%